2011
DOI: 10.3389/fmicb.2011.00127
|View full text |Cite
|
Sign up to set email alerts
|

Soil Bacteria and Fungi Respond on Different Spatial Scales to Invasion by the Legume Lespedeza cuneata

Abstract: The spatial scale on which microbial communities respond to plant invasions may provide important clues as to the nature of potential invader–microbe interactions. Lespedeza cuneata (Dum. Cours.) G. Don is an invasive legume that may benefit from associations with mycorrhizal fungi; however, it has also been suggested that the plant is allelopathic and may alter the soil chemistry of invaded sites through secondary metabolites in its root exudates or litter. Thus, L. cuneata invasion may interact with soil mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 68 publications
5
35
0
Order By: Relevance
“…First, OTU relative abundance within a sample was calculated by dividing the fluorescence intensity of an individual peak by the total intensity of the electrophoretic profile (sum of the intensity of all peaks). This step allows correcting for possible run to run variability in fluorescence signal that may arise during capillary electrophoresis (Yannarell et al, 2011). Data were then square-root transformed to minimize the influence of dominant OTUs on the sample ordination.…”
Section: Microbial Community Structurementioning
confidence: 99%
“…First, OTU relative abundance within a sample was calculated by dividing the fluorescence intensity of an individual peak by the total intensity of the electrophoretic profile (sum of the intensity of all peaks). This step allows correcting for possible run to run variability in fluorescence signal that may arise during capillary electrophoresis (Yannarell et al, 2011). Data were then square-root transformed to minimize the influence of dominant OTUs on the sample ordination.…”
Section: Microbial Community Structurementioning
confidence: 99%
“…Greene var. fasciculata from previously described locations (Yannarell et al 2011) at Ft. Benning, Georgia and Ft. Leonard Wood, Missouri. Root nodules were cleaned with 0.02 % polysorbate 20, surface sterilized with 6 % sodium hypochlorite and then rinsed with autoclaved DI water three times (Bender et al 1989).…”
Section: Methodsmentioning
confidence: 99%
“…1). Furthermore, our previous work has shown that high densities of invasive L. cuneata are correlated with shifts in overall soil bacterial community composition in comparison to uninvaded sites (Yannarell et al 2011). Further research is necessary before it can be established that these belowground changes can reinforce L. cuneata invasion, but our current results indicate that changes to the composition of nitrogenfixing rhizobacteria in invaded habitats could lead to asymmetrical benefits for L. cuneata over its native congeners.…”
Section: Asymmetrical Benefit Of Microbial Mutualists To Native and Imentioning
confidence: 96%
See 1 more Smart Citation
“…DGGE is one of the important approaches to study the shifts in soil microbial communities subject to various kinds of stresses. As such, this technique has been used in several studies carried out to assess the impact of invasive plant species on soil microbial community (e.g., Nie et al 2010;Yannarell et al 2011;Zhang et al 2010). The fundamental question asked in the present study was whether or not C. sumatrensis alters soil microbial communities in the urban ecosystems of the Kashmir Himalaya.…”
Section: Introductionmentioning
confidence: 99%